Are current debt relief initiatives an option for scaling up health financing in beneficiary countries? - M Kaddar; E Furrer
One central goal of the enhanced Heavily Indebted Poor Countries (HIPC) Initiative and the more recent Multilateral Debt Relief Initiative (MDRI) is to free up additional resources for public spending on poverty reduction. The health sector was expected to benefit from a considerable share of these funds. The volume of released resources is important enough in certain countries to make a difference for priority programmes that have been underfunded so far. However, the relevance of these initiatives in terms of boosting health expenditure depends essentially, at the global level, on the compliance of donors with their aid commitments and, at the domestic level, on the success of health officials in advocating for an adequate share of the additional fiscal space. Advocacy efforts are often limited by a state of asymmetric information whereby some ministries are not well aware of the economic consequences of debt relief on public finances and of the management systems in place to deal with savings from debt relief. A thorough comprehension of these issues seems essential for health advocates to increase their bargaining power and for a wider public to readjust expectations of what debt relief can realistically achieve and of what can be measured. This paper intends to narrow the information gap by classifying debt relief savings management systems observed in practice. We illustrate some of the major advantages and stated drawbacks and outline the policy implications for health officials operating in the countries concerned. There should be careful monitoring of fungibility (i.e. where untraceable funds risk substitution) and additionality (i.e. the extent to which new inputs add to existing inputs at national and international level).